Makna Kalimat Amr dan Nahy dalam Kitab Bidāyat al-Hidāyah Karya Imam Al-Ghazālī - Puspita, Rani; Yusup, Maulana (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This article aims to explore various meanings within the sentences of